2011
DOI: 10.1117/12.876496
|View full text |Cite
|
Sign up to set email alerts
|

The use of a high-order MEMS deformable mirror in the Gemini Planet Imager

Abstract: We briefly review the development history of the Gemini Planet Imager's 4K Boston Micromachines MEMS deformable mirror. We discuss essential calibration steps and algorithms to control the MEMS with nanometer precision, including voltage-phase calibration and influence function characterization. We discuss the integration of the MEMS into GPI's Adaptive Optics system at Lawrence Livermore and present experimental results of 1.5 kHz closed-loop control. We detail mitigation strategies in the coronagraph to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In order to suppress waffle and reduce edge effects, during Integration and Test a modified Tweeter influence function filter was put in place. As discussed elsewhere, 22 the estimated phase is pre-compensated by a influence function filter to correctly shape the phase on the Tweeter. Due to the broadness of the Tweeter influence function, the effective Tweeter gain for high spatial frequencies 23 is very small.…”
Section: On-sky Resultsmentioning
confidence: 99%
“…In order to suppress waffle and reduce edge effects, during Integration and Test a modified Tweeter influence function filter was put in place. As discussed elsewhere, 22 the estimated phase is pre-compensated by a influence function filter to correctly shape the phase on the Tweeter. Due to the broadness of the Tweeter influence function, the effective Tweeter gain for high spatial frequencies 23 is very small.…”
Section: On-sky Resultsmentioning
confidence: 99%
“…We found that there is a sweet spot for the separation between the DMs at an inter-DM Fresnel number of 576. Using this separation with 64x64actuator DMs, which are already commercially available, 13 allows us to achieve ∼ 10 −10 contrast averaged over the dark hole for an on-axis point source. This is also roughly where the best throughput is found.…”
Section: Discussionmentioning
confidence: 99%
“…While space-based telescopes avoid those atmospheric disturbances, their light-weighted and therefore floppy primary mirrors may induce aberrations which vastly reduce the telescope performance [1]. In terrestrial telescopes, the use of deformable mirrors to overcome the atmospheric seeing limit is well established [2,3], many types of deformable mirrors are commercially available [4,5].…”
Section: Introductionmentioning
confidence: 99%